1989
DOI: 10.1111/j.1432-1033.1989.tb14855.x
|View full text |Cite
|
Sign up to set email alerts
|

Human gastric lipase

Abstract: Human gastric lipase subjected to limited tryptic proteolysis lost its ability to hydrolyze emulsified long‐chain triacylglycerol. Activity against a water‐soluble substrate was however retained, indicating that proteolysis did not affect the active site. Sequence analysis revealed that trypsin specifically cleaved the linkage between lysine‐4 and leucine‐5. This cleavage rendered the enzyme unable to bind to emulsified triacylglycerol particles, e.g. human milk fat globules. We suggest that the N‐terminal tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This suggests that, despite proteolysis, capacity to hydrolyse substrates is retained in smaller fragments, whereas recognition and hydrolysis of the phospholipid emulsified lipid substrates depends on a more intact HSL molecule. Analyses of both lipoprotein lipase (LPL) [43] and gastric lipase (GL) [44] during proteolysis, have similarly shown that lipase activity is affected more than esterase activity during proteolysis. The fact that TO activity declines more rapidly than CO and MOME activities, can be explained by differences in substrate accessibility at the interface of the different lipid emulsions.…”
Section: Limited Proteolysis and Denaturationmentioning
confidence: 99%
“…This suggests that, despite proteolysis, capacity to hydrolyse substrates is retained in smaller fragments, whereas recognition and hydrolysis of the phospholipid emulsified lipid substrates depends on a more intact HSL molecule. Analyses of both lipoprotein lipase (LPL) [43] and gastric lipase (GL) [44] during proteolysis, have similarly shown that lipase activity is affected more than esterase activity during proteolysis. The fact that TO activity declines more rapidly than CO and MOME activities, can be explained by differences in substrate accessibility at the interface of the different lipid emulsions.…”
Section: Limited Proteolysis and Denaturationmentioning
confidence: 99%
“…The binding mechanism of gastric lipase to emulsified TAG is not completely elucidated, but involves conformational changes in a lid domain that controls access to the active site upon lid opening (40,41). The N-terminal tetrapeptide has also been shown to be important for binding to long chain TAG emulsions (42). This probably involves the N-terminal hydrophobic residues (Leu-Phe) that are part of the interfacial recognition site, and also the presence of a charged residue (Lys4), that is involved in the stabilisation of the lid domain via a salt bridge with Glu225 present in the lid (41).…”
Section: Human Gastric Lipasementioning
confidence: 99%
“…A dog recombinant lipase, rGL, was produced to test this concept153 and was developed by the French company Meristem Therapeutics SA, Clermont-Ferrand (Merispase), that went out of business in September 2008. This approach is problematic for several reasons: gastric lipase specific activity is about 10 times lower than that of pancreatic lipase (measured on tributyrin);51 it is highly sensitive to trypsin proteolysis;154 and endogenous secretion of gastric lipase can be increased in patients with pancreatic insufficiency28 because of possible nutritional adaptation 98,155. However, gastric lipase supplements may still be a viable option.…”
Section: Future Developments For An Optimal Therapymentioning
confidence: 99%